2022
DOI: 10.30684/etj.2022.132300.1103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curing Temperature and Chemical Admixture Type on Fresh Properties and Compressive Strength of Ultra High-performance Concrete

Abstract:  Three types of chemical admixtures and curing regimes were used with ultra-highperformance concrete (UHPC).  150 MPa compressive strength is secured after 72 hours using Hyperplast PC-202 and curing at 90ºC.  UHPC mixtures require high admixture dosages, resulting in prolonged setting time.The types of post-setting curing and high range water reducing (HRWR) admixture used in Ultra-High-Performance Concrete (UHPC) mixtures play significant roles in determining their rheological and mechanical properties. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The strength result was 151.2 MPa using heat curing at 90 °C. This finding agrees with references [17,21,33], which found that the compressive strength of UHPC was significantly affected by the temperature of curing water due to the rate of hydration increasing with increasing temperature. Moreover, the thermal water cure has a greater impact on t early ages, and the formation of hydrated structures is improved by a thermal curing regime.…”
Section: Twenty-eight Days Compressive Strengthsupporting
confidence: 93%
See 2 more Smart Citations
“…The strength result was 151.2 MPa using heat curing at 90 °C. This finding agrees with references [17,21,33], which found that the compressive strength of UHPC was significantly affected by the temperature of curing water due to the rate of hydration increasing with increasing temperature. Moreover, the thermal water cure has a greater impact on t early ages, and the formation of hydrated structures is improved by a thermal curing regime.…”
Section: Twenty-eight Days Compressive Strengthsupporting
confidence: 93%
“…The curing process is essential for UHPC to develop its desired mechanical and durability qualities. Due to the low water contents, it is essential to increase the hydration reactions using the restricted amount of internal water and to take major precautions to prevent any water loss due to evaporation [17]. Prem et al, [18] concluded that 48 hours post-moulding-out is the optimal time for heat curing of UHPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow table test conforming to ASTM C1437 determined the effects of SS and WG on mortars' workability [27,28]. Ovendried graded standard sand as per ASTM C778 was used [29].…”
Section: Flow Table Testmentioning
confidence: 99%